A Clinical Competency Framework for the Basic Package of Oral Care: Perceptions of Primary Oral Health Providers in Rural Nepal - Koirala, Bidhya; Acharya, Shreedhar; Spero, Laura; Mittal, Rakhi; Erchick, Daniel J. (Frontiers in Public Health, 2022)
Introduction: The basic package of Oral Care (BPOC) was developed to improve oral health care for underserved populations worldwide. However, systematic delivery of the BPOC has been difficult to achieve, and training efforts have in some cases contributed to proliferation of malpractice. Standard Competency Frameworks (CF), increasingly used in dental and medical education to improve quality assurance, have not been established to date for the BPOC. Methods: To evaluate provider perceptions of a BPOC-specific CF, in-depth interviews were conducted with 7 Primary Oral Health Providers (POHPs) and 5 Clinic Assistants working in the Jevaia Oral Health Care project (Jevaia) in Nepal. Participants were limited to providers who have used the CF. Interviews were audio recorded, transcribed in Nepali, and translated into English. A qualitative thematic analysis was applied through a multi-stage review process, and emergent themes were further grouped and categorized to draw final conclusions. Results: Findings were categorized into four groups: 1) “What is the CF to Me”: Respondents frequently conflated the CF with professional development training. These activities together were essentially felt to offer clear performance guidance and a pathway for learning. 2) “Relationship to the Work”: Respondents reported that the CF’s guidelines increased confidence, peer accountability, and job satisfaction. 3) “Practical Improvements”: Providers felt the CF improved their clinical skills, communication, crowd management, and teamwork. 4) “Community Impact”: Many participants felt that improved skills had led to a more efficient workflow, greater community acceptance, and increased utilization of services. ​​Conclusions: Clinicians broadly felt that the CF improved both their professional satisfaction and the quality of patient care. CFs should be considered integral to BPOC implementation, along with opportunities for continuous professional learning, and these activities will likely be most meaningful and impactful when recognized by government and other licensing bodies.